HERAPEUTIC ASPECTS OF POSTERIOR PARALYSIS IN SURTI GOATS - Patel, MD; Tyagi, KK; sorathiya, LM (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
An investigative study was conducted on Surti goat flock maintained under AICRP on goat improvement at Livestock Research Station, NAU, Navsari. A total 24 adult Surti goats (16 males and 8 females) over a period of four years (2010-2013) were presumptively diagnosed as posterior paralysis. Affected goats showed sudden onset of paralytic symptoms in one or both hind limbs or paralysis of lumber region along with incoordinated and swaying back gait, Few fecal samples were found positive for presence of eggs of Strongylus spp. FAMACHA score of clinically affected goats was between 3 and 4 which indicated mild to moderate anaemia. All affected goats were treated with Inj. Ivermectin @0.4mg/kg body weight followed by oral fenbendazole @10 mg/kg daily for 5 days. Goats with both hind limbs/lumbar paralyses were provided slings till sufficient weight bearing on both hind legs. All affected goats were given supportive treatment and oral supplementation of vitamins and minerals for 5-10 days. Except death of one female, all were survived and recovered completely after 10 days. Improvement in FAMACHA score was observed on 11th day of treatment. The present investigation suggested that sufficient dosage of selective anthelmantic along with proper care and management during paralytic phase in cases of parasite caused posterior paralysis result in better clinical recovery within 10 day in goats.
Keywords: Goats; posterior paralysis; therapeutic management